2019
DOI: 10.1007/s41669-019-0137-0
|View full text |Cite
|
Sign up to set email alerts
|

The Costs of Industry-Sponsored Medical Device Clinical Trials in Alberta

Abstract: ObjectiveOur objective was to describe the costs of industry-sponsored clinical trials for medical devices in Northern Alberta, Canada.MethodsWe used centralized data to identify all industry-sponsored medical device clinical trials initiated in Northern Alberta from 2012 to 2016. For each arm of each trial, we calculated the price of devices provided by the sponsor and the cost of clinical and administrative services that were incurred to clinically operationalize the treatment.ResultsOur sample consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The main limitation of this work can be identified in the difficulty of finding literature related to tests of experimental medical devices. This is mainly due to the high costs of their trials (Akpinar et al, 2019), unlike what happens with drugs whose tests are multiple, easier to perform and with more available results in the literature. This limitation translates into the difficulty to evaluate those criteria that instead could be better assessed if decision makers could rely on data and analyses from the scientific literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main limitation of this work can be identified in the difficulty of finding literature related to tests of experimental medical devices. This is mainly due to the high costs of their trials (Akpinar et al, 2019), unlike what happens with drugs whose tests are multiple, easier to perform and with more available results in the literature. This limitation translates into the difficulty to evaluate those criteria that instead could be better assessed if decision makers could rely on data and analyses from the scientific literature.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in a situation of ambiguity, uncertainty, and vagueness, the decision‐makers are called upon to evaluate three medical devices with very different clinical, technical, and sustainability characteristics but used for the same purpose. As an addition, decision‐makers, unlike what happens for drugs, do not have clinical studies and trials on medical devices (Akpinar et al, 2019) and this exacerbates ambiguity and uncertainty (Mathew, 2011).…”
Section: Methodology and Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Peer-reviewed data regarding medical device development costs in the United States are limited, though a comparison of Canadian device versus drug studies suggested that drug studies are between 3.8 to 12.1 times more costly on a per-patient basis than device studies. 26 There is limited data comparing the clinical trial startup process between device and pharmaceutical clinical studies, though Abbott et al performed a retrospective analysis of multicenter clinical trials via the Clinical Trials Transformation Initiative (CTTI), a publicprivate partnership that identifies generalizable and effective practices for clinical trials, which provides some comparison of pharmaceutical and device studies. 18 They noted hospital-based sites were more common for device company trials whereas academic sites were more common for pharmaceutical company trials.…”
Section: Key Differences Between Pharmaceutical and Device Developmentmentioning
confidence: 99%
“…The majority of physicians are willing to accept an improvement on current technology; however, their skepticism overrides their adoption of innovative techniques. [10][11][12][13][14][15][16][17] Furthermore, physicians are becoming increasingly aware of cost-effectiveness. This strategy discourages innovation, as innovation might not be viable economically at its early phase.…”
Section: Challengesmentioning
confidence: 99%